An Error Correction Model Analysis Of The Impact Of Foreign Direct Investment On Economic Growth In Saudia Arabia - Abdelrahman Mohamed Mohamed Saeed (Migration Letters, 2022)
The aim of this study is to examine the impact of foreign direct investment (FDI) on economic growth in Saudi Arabia by applying the cointegration and error-correction model to annual data for the period 2000-2020. The results of the Auto Regressive Distributive Lag (ARDL) bound test of cointegration show the existence of a long-run equilibrium in the model. The long-run regression results indicate that exports, openness, and government spending are statistically significant, while FDI has1 a positive impact on GDP, although the influence is not highly significant. However, in the short-run, the study manifested an evidence that FDI, openness, and government spending are statistically significant at 1% level of significance. The existence of a short-term relationship between economic growth (GDP) and FDI, openness, and government expenditure in the model is evident from the results of the error correction model. The calculated adjusted of the model reveals that 97% of variations in economic growth have been explained by variations in FDI, government expenditures, exports, and openness. Stability and Diagnostic Tests showed no serial correlation in the model. The findings of this study are important for Saudi economic policymakers to undertake effective measures that can promote and attract FDI, contribute to the diversity of income sources, and accelerate economic growth.